Fisheries-related Tourism in Southern Tyrrhenian Coastline. (10th June 2016) - Nicolosi, Agata; Sapone, Nicola; Cortese, Lorenzo; Marcianò, Claudio
Abstract: Among several possible development activities, the Fishery Local Action Groups (FLAGs), activated with the EC Regulation 1198/2006, can promote fisheries-related tourism activities that may represent a driving sustainable force, for economic local development in coastal areas, in line with the EU objectives of reducing the fishing effort and, at the same time, fisheries-related tourism. The main objective of this study is to analyze the trend of the territory of the "Stretto" Coast FLAG in Calabria to diversify the fishing activities, also through the comparison with the Aeolian Islands, which are part of the "Islands of Sicily" FLAG. The methodology includes direct surveys through privileged witnesses such as fishermen and fishing cooperatives of the two areas. The results show some differences: in the Aeolian Islands the practice of fisheries-related tourism activities is conducted continuously all the year, in a few cases the fishermen also offer accommodation; on the contrary, in Calabria in the "Stretto" Coast FLAG vessels are of larger dimensions and fishing tourism is occasional and not widespread. Adequate promotion and marketing, and policy support are lacking in both areas.